City of Farmers and Merchants: Beisan in the Palestine Mandate Period (1918-1948) - ʿAbbāsī, Muṣṭafá (Journal of Holy Land and Palestine Studies, 2015)
This article discusses the rise of Palestinian Beisan during the late Ottoman period and the British Mandate (1918-1948). The study shows that the city grew due to two main factors: the first was the reform and change in the ownership of land and the second was the construction of the Hejaz railway and its connection to Haifa in 1905. Beisan attracted migrants from many regions and became a flourishing Arab centre of the Jordan valley region. This situation continued until the 1948 War, the Arab city was destroyed to its foundations and in its place was founded the Israeli Jewish city of Beit Shean.